2003
DOI: 10.1345/aph.1d171
|View full text |Cite
|
Sign up to set email alerts
|

Possible Valacyclovir-Related Neurotoxicity and Aseptic Meningitis

Abstract: Healthcare providers should be aware of valacyclovir as a possible cause of drug-induced aseptic meningitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 15 publications
0
12
0
6
Order By: Relevance
“…Perhaps, because VACV is more rapidly absorbed, VAN may develop unexpectedly, especially in elderly patients and those with renal failure. Linssen-Schuurmans et al [3] first reported VAN in 1998, and they and others have reported 20 cases since then [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] (Table 1). ACV neurotoxicity usually appears within the first 24 to 72 h of treatment, with renal failure and neurotoxicity, and complete recovery usually follows within 2 to 7 days after treatment is discontinued [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps, because VACV is more rapidly absorbed, VAN may develop unexpectedly, especially in elderly patients and those with renal failure. Linssen-Schuurmans et al [3] first reported VAN in 1998, and they and others have reported 20 cases since then [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] (Table 1). ACV neurotoxicity usually appears within the first 24 to 72 h of treatment, with renal failure and neurotoxicity, and complete recovery usually follows within 2 to 7 days after treatment is discontinued [18].…”
Section: Discussionmentioning
confidence: 99%
“…Linssen‐Schuurmans et al. [3] first reported VAN in 1998, and they and others have reported 20 cases since then [3–17] (Table 1). ACV neurotoxicity usually appears within the first 24 to 72 h of treatment, with renal failure and neurotoxicity, and complete recovery usually follows within 2 to 7 days after treatment is discontinued [18].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, almost all authors do not report the specific clinical presentation of the occurring headache. In some cases, the headache is described to be global, progressive and intense [6], other patients have pressure-like pain [7], sometimes the headache is constant and frontally localized [8] and others have a recurrent headache [9]. Single case reports show that headache in aseptic meningitis might be migraine-like [10][11][12] and even sufficiently treated with subcutaneous application of sumatriptan [10].…”
Section: Clinical Presentation Of Headache In Drug-induced Aseptic Mementioning
confidence: 99%
“…Other antimicrobial drugs have been implicated in drug-induced aseptic meningitis [5], for example. amoxicillin [14,52,53], cephalosporins [26,54], rifampicin [28], valacyclovir [55], and ornidazole [56].…”
Section: Antimicrobial Drugsmentioning
confidence: 99%